Evolution of the Clinical Concept of Peruvian Wart between 1842 and 1871 - Sugizaki, Eduardo; Barbiani, Rosangela; Asquidamini, Fabiane (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
A new history of medical knowledge on Carrion's disease is presented. In a preliminary review of historiography (since 1885), we have found: 1) until 'Oroya fever'(1871), only an eruptive disease, the Peruvian wart, was known; 2) in 1875, Peruvian physicians proposed both should be the same; 3) in 1885, Daniel Carrión. A global clinical description of the disease was already known in 1842-1871. Some obstacles to the knowledge of the disease were the diversity and inconstancy of general and local symptoms: 1) difficult comprehensive understanding of manifestations; 2) suggesting a constant complication of malaria; 3) precluding analogy with eruptive fevers. These were overcome previously and independently from the 'Oroya fever'. It allowed symptoms that a shallow empiricism kept separated as isolated pathological phenomena, favoring clinical differential diagnosis between the diseases. This study contributed to a greater understanding of mechanisms of building of nosologic unity in the Clinical Age of medicine.